Is distal segment ostectomy essential for stabilization of the condylar position in patients with facial asymmetry? - Ki Eun Hong; Eun Sup Shin; Jun Park; Ji Eon Yun; Chul Hoon Kim; Jung Han Kim; Bok Joo Kim (SpringerOpen, 2021)
Abstract Background The purpose of this retrospective study was to evaluate the postoperative change in the position and stability of the mandibular condyle after bilateral sagittal split ramus osteotomy (BSSRO) and BSSRO with distal segmental ostectomy (DSO) in patients with facial asymmetry using 3D computed tomography. Methods The condyles of the patient diagnosed with facial asymmetry were divided into the deviated side (DS) and the non-deviated side (NDS). Group I, which was treated with BSSRO only, and Group II, which additionally received DSO along with BSSRO, were superimposed on the condyle using the pre-and postoperative 3D CT. The amount of condylar change in anteroposterior displacement, mediolateral displacement, and rotation was measured. The clinical symptoms of temporomandibular joint were also evaluated before and after surgery for each patient. Results Between Groups I and II, there was no statistically significant difference in the anteroposterior condylar position on both DS and NDS. And also, there was no statistical difference between the two groups in the mediolateral change on DS but, statistically significant difference on NDS. The change in the rotation of the condyle was observed to rotate inward from both condylar heads of Groups I and II, and a statistically significant difference was observed between the two groups on both DS and NDS. Moreover, no difference in clinical temporomandibular joint symptoms was observed after surgery in each DS and NDS condyle of the two groups. Conclusions As a result of analyzing the condylar position change of the group treated with BSSRO alone and the group treated with BSSRO and DSO in patients with facial asymmetry, there were statistically significant differences in the mediolateral displacement of NDS and the condyle rotation of NDS and DS. However, the anteroposterior condylar position did not show any difference in the bilateral condyles. In addition, since worsening clinical symptoms of bilateral temporomandibular joint were not observed before and after surgery in both groups, it is concluded that it is not necessary to accompany DSO in patients with facial asymmetry (minimum 3 mm, maximum 7 mm).